2021
DOI: 10.3390/cancers13030396
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Recurrent Genetic Aberrations in Multiple Myeloma

Abstract: Oncogene activation and malignant transformation exerts energetic, biosynthetic and redox demands on cancer cells due to increased proliferation, cell growth and tumor microenvironment adaptation. As such, altered metabolism is a hallmark of cancer, which is characterized by the reprogramming of multiple metabolic pathways. Multiple myeloma (MM) is a genetically heterogeneous disease that arises from terminally differentiated B cells. MM is characterized by reciprocal chromosomal translocations that often invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 305 publications
(370 reference statements)
0
27
2
Order By: Relevance
“…Compared to normal plasma cells, MM cells have enhanced metabolic activity including glycolysis, serine synthesis pathway (SSP), glutaminolysis, fatty acid or β-oxidation all benefiting tumor cells against oxidative damage (Figure 3) [131].…”
Section: Metabolism Rewiringmentioning
confidence: 99%
“…Compared to normal plasma cells, MM cells have enhanced metabolic activity including glycolysis, serine synthesis pathway (SSP), glutaminolysis, fatty acid or β-oxidation all benefiting tumor cells against oxidative damage (Figure 3) [131].…”
Section: Metabolism Rewiringmentioning
confidence: 99%
“…MYC has been described as a protooncogene involved in many cancers, including leukemia and lymphoma [5][6][7]. In MM, it is known that aberrant expression of MYC is due to recurrent chromosomal alterations [8] and previous studies have demonstrated that its expression is involved in MM progression from early stages of plasma cell dyscrasias, including monoclonal gammopathy of unknown significance (MGUS) and smoldering multiple myeloma (SMM), to MM [9]. Several authors have reported that MYC deregulation is involved in disease progression and has been related with poor progression-free survival in MM patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report that elevated mtDNACN, which reflects the abundance of mitochondria, is an additional feature of MM. Our data provide evidence that the malignant transformation of myeloma cells is coupled to the activation of mitochondrial biogenesis, resulting in increased mtDNA levels [3][4][5] and mtDNACN changes [6,8,9]. Indeed, mtDNA can define early and late tumor progression in MM [12].…”
Section: Discussionmentioning
confidence: 67%
“…Mitochondria appear to be essential for tumor formation and growth [6], and dysfunction in mitochondrial processes affects the electron transport chain and promotes tumor metastasis [7]. Indeed, cancer is characterized by altered energy metabolism involving not only genetic alterations in nuclear DNA, but also mtDNA mutations and changes in mtDNACN [6,8,9]. A recent comprehensive study of the mtDNACN in many cancer types revealed that the majority show changes in mtDNA content when compared with adjacent healthy tissue [9], and also that the mtDNACN is significantly associated with patient survival.…”
Section: Introductionmentioning
confidence: 99%